A Case Report on Anomalous Origin of Left Coronary Artery from Pulmonary Artery in a Child - Nakul Pathak; Vineeta Pande; Mrinali Thakur; Shailaja Mane (Medical Journal of Dr. D.Y. Patil Vidyapeeth, 2024)
Anomalous left coronary artery from the pulmonary artery (ALCAPA) is a rare but fatal congenital cardiovascular disease. In this condition, the left coronary artery originates from the pulmonary artery, which should actually originate from the ascending aorta. This causes left ventricular dysfunction/insufficiency. Many a times it is asymptomatic and is missed during the initial months of life. Incidence is 1 in 300000 live births and comprises about 0.25–0.5% of congenital heart disease. In this article, we present a case of a 4-month-old infant who came with complaints of fever and increased work of breathing. On examination, there were signs of respiratory distress. Systemic examination was normal. Electrocardiogram findings showed inverted T waves in leads 1 and aVL, and in leads V5-V6, elevated ST segments were noted. Patient was suspected to have ALCAPA, and the echocardiogram confirmed the diagnosis. Patient was planned for surgery. ALCAPA is a clinical diagnostic challenge as it presents with similar complaints of common pediatric diseases such as bronchiolitis, failure to thrive, gastroesophageal reflux, and cardiomyopathy. Usually, majority of affected children remain undiagnosed and die within the first year of life. Hence, it is of utmost importance to keep a watch for this condition for early diagnosis and surgical intervention which will help in improving the prognosis.